The impact of rotavirus vaccination in the prevalence of gastroenteritis and comorbidities among children after suboptimal rotavirus vaccines implementation in Taiwan: A population-based study. Issue 25 (25th June 2021) - Lu, Meng-Che; Shia, Ben-Chang; Kao, Yi-Wei; Lin, Sheng-Chieh; Wang, Chuan-Yu; Lin, Wen-Chuan; Chen, Shih-Yen
Abstract : Abstract: In Taiwan, rotavirus vaccination was implemented in 2006 in the private sector. The population-based impact of rotavirus vaccination on gastroenteritis and comorbidities of children remains under-investigated. We analyzed the annual prevalence of rotavirus-related disease, including gastroenteritis, convulsions, epilepsy, type I diabetes mellitus, intussusception, and biliary atresia among children under 5 years of age. Data were collected from Taiwan's National Health Insurance Research Database, a nationwide population-based database. A 16-year retrospective cohort study was conducted between 2000 and 2015. Among children <5 years of age, the prevalence of gastroenteritis decreased after 2012 (44, 259.69 per 100 thousands) and remained lower through 2015 (39, 931.11per 100 thousands, P < .001). The prevalence of convulsions rose steadily and significantly from 2007 (775.90 per 100 thousands) to 2015 (962.17 per 100 thousands, P < .001). The prevalence of epilepsy decreased significantly until reaching a nadir in 2013 (from 501.56 to 293.53 per 100 thousands, P < .001). The prevalence of biliary atresia tended upward, and surged suddenly in 2007 with a peak in 2013 (18.74 per 100 thousands). Among infants (<1 year of age) from 2000 to 2015, the prevalence of gastroenteritis declined steadily, and more rapidly after 2007 (22, 513 to 17, 285 per 100 thousands). In Taiwan, after introducing rotavirus vaccination, gastroenteritis in young children decreased, especially in infancy. However, gastroenteritis is still common in children, given other emerging pathogens. Our results highlight the impact of rotavirus vaccines on children's health in Taiwan and provide indications for future preventive medicine and healthcare strategies in children.